1989
DOI: 10.1079/bjn19890103
|View full text |Cite
|
Sign up to set email alerts
|

The Kilkenny Health Project: food and nutrient intakes in randomly selected healthy adults

Abstract: 1. Sixty healthy subjects aged 3-years (thirty men and thirty women) were randomly selected from electoral registers to participate in a dietary survey using the 7 d weighed-intake method during June-August 1985.2. Energy intake (MJ/d) was 123 for men and 8.4 for women. Fat contributed 36.0 and 39.1 % of the total energy intake of men and women respectively. When this was adjusted to exclude energy derived from alcoholic beverages, the corresponding values were 38.8 and 39.7 % respectively. The major sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 6 publications
5
14
1
Order By: Relevance
“…High alcohol intake was associated with lower risk of high FAT% and FATres and, after multivariate adjustment including energy, also with lower risk of high FATg, in both women and men. This relation has been observed in other studies (Gibney et al, 1989;Hulshof et al, 1991) and may partly be an effect from alcohol's contribution to total energy intake. In Sweden, and several other countries, nutrient recommendations have been reformulated and are presently based on macronutrient composition calculated from non-alcohol energy.…”
Section: Underreporting Of Energysupporting
confidence: 84%
“…High alcohol intake was associated with lower risk of high FAT% and FATres and, after multivariate adjustment including energy, also with lower risk of high FATg, in both women and men. This relation has been observed in other studies (Gibney et al, 1989;Hulshof et al, 1991) and may partly be an effect from alcohol's contribution to total energy intake. In Sweden, and several other countries, nutrient recommendations have been reformulated and are presently based on macronutrient composition calculated from non-alcohol energy.…”
Section: Underreporting Of Energysupporting
confidence: 84%
“…Thus, the present study does not set out to examine income effects on eating habits, nor is it implied that the study population are representative of social classes five and six in general, employed or otherwise. The values for energy intake recorded in the present study are in broad agreement with those of other studies of free-living Irish adults Barker et al, 1989;Gibney et al, 1989;Lee & Cunningham, 1990). However, the intakes of iron and vitamin C for both sexes and of fibre by women were lower than previously reported for Irish adults.…”
Section: Discussionsupporting
confidence: 82%
“…Generalized dietary advice is issued in Ireland as in many European countries (Food Advisory Committee, 1984) and is attempting to translate quantitative dietary goals into practice. The existing evidence suggests that many of these goals are difficult to achieve (Black et 01.. 1984;Nelson, 1985; Gibney et al, 1989). Whilst the factors influencing the uptake of nutritional advice are complex (Guthrie, 1987), two key factors which would conceivably influence such uptake are poverty and educational status with the lower socio-economic groups apparently most in need of nutrition intervention programmes.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of vitamin A, the lower intakes are of no concern because in both studies intakes were well above the RDA of 750 pg. Similarly, while the average intake of vitamin C in Tallaght males (Lee & Gibney, 1988) was 30 mg below the Kilkenny males (Gibney et al 1989), this lower intake was in line with the RDA and an examination of the distribution of intakes showed that only 19% had intakes below 75% RDA.…”
Section: A D U L T S >18 Y E a R Smentioning
confidence: 93%
“…In Table 4 mean nutrient intakes of adult males in the Tallaght Study of low-income families (Lee & Gibney, 1988) are compared with similar data recorded for adult males of mixed social classes studied in the Kilkenny Health Project (Gibney et al 1989). As can be seen the intakes of energy, protein, fat, fibre and Fe are very similar, Ca intakes are higher in the Tallaght group (Lee & Gibney, 1988), due to a higher milk consumption, but intakes of other micro-nutrients are lower.…”
Section: A D U L T S >18 Y E a R Smentioning
confidence: 94%